2000
DOI: 10.1002/1097-4636(200102)54:2<272::aid-jbm15>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion peptide modification of gold-coated polyurethanes for vascular endothelial cell adhesion

Abstract: Gold-coated polyurethanes were chemisorbed with three cell-adhesion peptides having an N-terminal cysteine: cys-arg-gly-asp (CRGD), cys-arg-glu-asp-val (CREDV), and the cyclic peptide cys-cys-arg-arg-gly-asp-try-leu-cys (CCRRGDWLC). The peptides were selected based on their presumed preferential interactions with the cell-surface integrins on vascular endothelial cells. The ability of the surfaces to support the preferential adhesion of human vascular endothelial cells was studied by comparing in vitro adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 36 publications
(65 reference statements)
3
28
0
Order By: Relevance
“…To block the empty AuNp surface, 100 L of 10% BSA (in DI water) was added into the mixture solution, followed by shaking the mixture for 1 h. The unbound antibodies and BSA were removed by centrifuging the solution at 12,000 rpm for 1 h at 4 • C. Finally, the precipitate was dissolved in 1 mL of 1 × PBS (pH 8.0) containing 0.1% NaN 3 until used for immunoassay. Based on the previous literatures [27,28], it was reported that the binding of antibodies to AuNps was established through electrostatic interaction or ionic/hydrogen bonding between the surface-terminated anionic groups (-COO-) on the nanoparticles and the positively charged amino groups (-NH 3 + ) of the lysine residues of the protein. Because the lysine residues including amino groups are abundant and distributed over the entire antibody, it results in blocking the epitope during the conjugation.…”
Section: Antibody Conjugation To the Gold Nanoparticlesmentioning
confidence: 99%
“…To block the empty AuNp surface, 100 L of 10% BSA (in DI water) was added into the mixture solution, followed by shaking the mixture for 1 h. The unbound antibodies and BSA were removed by centrifuging the solution at 12,000 rpm for 1 h at 4 • C. Finally, the precipitate was dissolved in 1 mL of 1 × PBS (pH 8.0) containing 0.1% NaN 3 until used for immunoassay. Based on the previous literatures [27,28], it was reported that the binding of antibodies to AuNps was established through electrostatic interaction or ionic/hydrogen bonding between the surface-terminated anionic groups (-COO-) on the nanoparticles and the positively charged amino groups (-NH 3 + ) of the lysine residues of the protein. Because the lysine residues including amino groups are abundant and distributed over the entire antibody, it results in blocking the epitope during the conjugation.…”
Section: Antibody Conjugation To the Gold Nanoparticlesmentioning
confidence: 99%
“…Hegemann et al, determined that this environment promotes endothelial cell attachment and growth [102]. Similarly, other cell-adhesion peptides, such as glycine-arginine-glycine-aspartate (GRGD), immobilized on the surface of biomaterials have displayed enhanced endothelial cell attachment [103][104][105][106]. Pre-absorbed proteins, such as fibronectin, laminin and gelatin, present on polymer surfaces have been shown to increase cell attachment, but may reduce cell proliferation [107,108].…”
Section: Attachment Of Pharmaceuticals Biopharmaceuticals or Biomolementioning
confidence: 99%
“…This endogenous attachment mechanism is directly affected by surface chemistry, providing a correlation between the substrates and their effect on cell adhesion [33]. However, since protein adsorption cannot be prevented in vivo when materials are in contact with various tissues and blood, we have also carried out studies using the M-3T3 cells in serumcontaining medium, as these cells cannot be grown in the absence of serum proteins [34][35][36].…”
Section: Detection Of Cell Adhesion Using Unmodified Gold Surfacesmentioning
confidence: 99%
“…To further evaluate the potential application of dendronized surfaces in tissue engineering and blood-contacting applications, to examine the effect of the presence of serum proteins on cellular responses to these materials, and to build upon previous studies postulating that the formation of a confluent vascular endothelial cell monolayer significantly improves the blood-contacting properties of biomaterials [35], we chose to study the adhesion of mouse 3T3 fibroblasts (M-3T3). The ability of the dendronized surfaces to support cell interactions in the presence of serum proteins, perhaps better simulating in vivo conditions, was investigated by conducting the adhesion studies of M-3T3 cells in serum-containing medium.…”
Section: In Vitro Adhesion Studies Of Mouse 3t3 Fibroblasts (M-3t3)mentioning
confidence: 99%